Perioperative changes in superficial pelvic organ prolapse quantification system measurements after prolapse surgery. Issue 2 (18th March 2019) - Durnea, Constantin M.; Basu, Maya; Dadhwal, Kiran; Gayle, Yasmin V.; Gauthaman, Nivedita; Khunda, Azar; Doumouchtsis, Stergios K.
Abstract: Objectives: To evaluate the values of perineal body (PB) and genital hiatus (GH) before and after posterior repair. We also evaluated the introital surface area (ISA)—a sum of transverse and longitudinal GH measurements. Methods: This secondary analysis of a prospective case series included 94 women undergoing posterior vaginal prolapse surgery at a consultant urogynecology clinic between October 3, 2011, and October 2, 2014. Patients were examined in clinic using the pelvic organ prolapse quantification system with Valsalva maneuver, and in theatre pre‐ and postoperatively with traction. Results: Immediately postoperatively, a statistically significant change (all P <0.001) was noted for GH (mean difference −0.59 cm), PB (−0.56 cm), and ISA (−0.87 cm) compared with preoperative measurement. This effect was maintained for GH (−0.42 cm) and PB (−0.40 cm) at 2 months' follow‐up (both P <0.001), and for PB alone (−0.43 cm; P =0.04) at 8 months. ISA had a moderate correlation with GH ( r =0.55). Conclusions: Posterior repair significantly improved PB length at months 2 and 8, and GH length at month 2. ISA did not correlate with prolapse stage. Changes in GH were not maintained beyond postoperative month 2. Abstract : Posterior repair was associated with significant improvements in perineal body length at 2 and 8 months' follow up, and genital hiatus length at 2 months' follow up.